Contrast-Enhanced Subtraction Harmonic Sonography for Evaluating Treatment Response in Patients with Hepatocellular Carcinoma - Ding, Hong; Kudo, Masatoshi; Onda, Hirokazu; Suetomi, Yoichiro; Minami, Yasunori; Maekawa, Kiyoshi (American journal of roentgenology (1976), 2001)
Our objective was to assess the usefulness of contrast-enhanced subtraction harmonic sonography in evaluating the treatment response of patients with hepatocellular carcinoma. Thirty-two hepatocellular carcinoma lesions in 26 patients (age range, 44-85 years; mean age, 66 years) were examined with Levovist-enhanced intermittent harmonic imaging before and after therapy. A Toshiba Powervision 8000 was used. A subtraction image was obtained by digitally subtracting the last-frame harmonic image from the first-frame image when multishot mode was preset. Results of contrast-enhanced CT were compared with the results of subtraction harmonic imaging. Before therapy, an enhancement pattern of tumor vascularity was seen for 93.8% (30/32) of hepatocellular carcinoma nodules on subtraction harmonic imaging. After therapy, subtraction harmonic imaging showed 46.7% (14/30) enhancement (incomplete tumor necrosis) and 53.3% (16/30) no enhancement (complete tumor necrosis). When dynamic CT was the gold standard, the sensitivity, specificity, and accuracy of subtraction harmonic imaging were 93.3%, 100%, and 96.7%, respectively. Intratumoral flow signals in hepatocellular carcinoma after therapy on harmonic imaging were used as a guide to target additional percutaneous therapy. Digital subtraction contrast-enhanced harmonic imaging can depict tumor vascularity in hepatocellular carcinoma after therapy sensitively and accurately. Because it is easy to perform and provides real-time needle insertion guidance, it may be preferable to perform after localized therapy to monitor treatment response, which will reduce unnecessary CT scanning.